On the lexemes uchodźca and the derivatives of it in the light of Polish lexicography and corpus texts - Witaszek-Samborska, Małgorzata; Piotrowicz-Krenc, Anna (Porównania, 2025)
The article is devoted to the lexeme uchodźca and the derivatives of it in the history of the Polish language based on lexicographic and corpus data. The appearance of the derivative uchodźca from the verb uchodzić in the 19th century was preceded by other derivatives – uchodzień and uchodnik. The nouns uchodźczyni and uchodźstwo and the adjective uchodźczy also had their earlier variants: uchodnia, uchod and uchodni. In contemporary Polish, uchodźca and the derivatives of it are words with high textual frequency. This is a reflection of the geopolitical situation in the world in Polish of the 21st century. The most frequent collocations with bases in the form of the above-mentioned lexemes allow us to reconstruct the image of refugees and exile in ethnic, economic, social, and legal-political aspects. The increase in the frequency of the feminative uchodźczyni and the appearance of the expression osoba uchodźcza in 21st century texts indicate cultural changes reflected in the inclusive language.